Marketing Efficiency of Patin Fish in Belitang District, East OKU Regency - Sinta Arzaniah; Munajat Munajat; Yetty Oktarina (Cita konsultindo, 2024)
Catfish is a type of freshwater fish that is much sought after by the public. This fish is in great demand as a culinary menu because it has the lowest fat content compared to other types of fish. This research will be carried out in Patin village, precisely in Belitang District, East OKU Regency. The location determination was carried out purposively considering that Belitang District, East OKU Regency is the center for catfish cultivation in South Sumatra, especially East OKU. The research method used in this research is the survey method. The sampling method used in this research is the census method. There are two marketing institutions involved in the catfish marketing channel in Belitang District, East OKU Regency, including wholesalers and retailers. Analysis of the data processed in the research is primary and secondary data. Primary data is used to analyze marketing efficiency as seen from marketing margin, producer share and price transmission elasticity. Secondary data was used to analyze the marketing channels for catfish in Belitang District, while to answer the first research problem, marketing margin analysis was used and to answer the second problem formulation, efficiency analysis was used. Based on the research results, there are two marketing channels in Belitang District, East OKU Regency. That the marketing margin obtained for marketing channel I was IDR 5,275 for large traders and IDR. 4,725,- at retailers. Efficient marketing channels in marketing channels II. Marketing channel II is the lowest marketing margin. The low margin value obtained is due to the absence of profit calculations for each institution, where in this channel there are no institutions involved.